The New Perspective of Exercise as a Breast Cancer Therapy - Alvin Wiharja (Journal of Medicine and Health, 2016)
The prevalence of cancer increases each year, from 4.7‰ in 2007 to 5 ‰ in 2013. InWest Java, the prevalence of cancer is quite high at 1.0 ‰. Obesity becomes a risk factor forcancer. Exercise is aimed to solve the obesity problem, prevent and improve the cancer patientcondition, as well as improve the quality of life of cancer patients. Exercise plays a role in thetreatment of cancer patients. The potential benefits obtained during and after exercise areincrements of strength, speed, muscle mass, physical functions, range of motions, immunefunctions, the average completeness of chemotherapy, improved body shape, moods andconfidence. For patients diagnosed with breast cancer, exercise acts as a therapeutic to preventthe disease and its etiology factors (hormonal theory, the theory of immunity and inflammationtheory). Applying the proper exercise (frequency, intensity, type and time) in cancer patientswould improve the physical performance which is impaired due to cancer. Exercise canimprove levels of fitness, muscle strength, quality of life and fatigue in patients with cancersurvivors. Diagnosis and management of cancer can decrease the system performance organsand it would be upgrade by good exercise.Keywords: breast cancer,exercise